A case developing bilateral bullae due to COVID-19 infection and operated for recurrent pneumothorax - Ersöz Köse, Elçin; Boyacıoğlu, Kaan Ayberk; Alparslan Bekir, Sümeyye; Atinkaya Baytemir, Cansel; Yalçınkaya, İrfan (The European Research Journal, 2023)
In December 2019, a novel coronavirus (COVID-19) pneumonia emerged in Wuhan, China and has rapidly spread to multiple countries worldwide. Pulmonary parenchymal opacities are often observed during chest radiography. Pneumothorax was reported in 1% of patients in studies. In this paper, we aimed to present a patient with a history of long-term hospitalization in intensive care unit due to COVID-19 pneumonia who was operated for right recurrent pneumothorax secondary to COVID-19 after discharge.